O processo de comunicação organizacional e a avaliação institucional na Universidade Federal da Paraíba - Ventura, Elizete (2021)
This work aims to understand the conception and functioning of communication processes within the Federal University of Paraíba (UFPB) and its relations with Institutional Evaluation. For this, the theoretical framework used in this work contemplated the theme “communication processes and Institutional Assessment, instituted by the National Higher Education Assessment System (SINAES). The theoretical basis on communication considered, especially, the studies of Margarida M. Krohling Kunsch (2003, 2009 and 2016). On the subject of evaluation, we used the studies of José Dias Sobrinho (2003), Dilvo Ilvo Ristoff (2019), among others, in addition to the specific legislation for the evaluation of higher education. In order to achieve the general objective of this research, this study chose to bring the functioning of communication management at UFPB into question. As a methodology of the work, a bibliographic and documentary study was carried out. The content analysis of the documentary study was carried out through the analysis of the last two Institutional Development Plans (PDI's) of UFPB (2014-2018 and 2019-2023), the Self-Assessment Reports of 2017, 2018 and 2019 and the Institutional Assessment Instrument 2017 external survey, in which we cross-check data. Based on the nature, this research was of the applied type; based on the objectives, this study consisted of a descriptive and exploratory research. As for the approach to the problem, it was classified as a qualitative research. As for the adopted methods of procedure, they had a transition between the bibliographic study and the documentary study. Thereby, in view of the results obtained, we have drawn up a list of suggestions for improvement. We conclude that there are weaknesses in the UFPB Communication, especially with regard to the communication management planning elaborated in the last two IDPs of this institution, as well as with regard to the evaluation process carried out by the CPA of UFPB, because of the three RAAI's evaluated by us, there was practically no evaluation of the communication. Finally, we hope to contribute to the UFPB communication process in order to improve the Institutional Assessment.